Pelatihan Pembuatan Totebag Tie-dye sebagai Upaya Pemberdayaan Ekonomi Kreatif di Desa Suka Jaya - Ayu Maya Lestari; Ayu Meldiana; Ayu Sinta Indriani; Ayu Vadia Aprilia; Azkia Putri Andini; Bintang Shavira Zahra; Khodijah Khodijah (Wisanggeni: Jurnal Pengabdian Masyarakat, 2026)
The problems faced by rural communities include limitations in access to information, training, and assistance that can support the development of the creative economy. These limitations have caused some rural communities to be unable to optimize their potential to improve family economic welfare independently. Therefore, this Community Service (PKM) activity aims to enhance the knowledge and skills of the productive-age housewife group who are members of the PKK organization in Suka Jaya Village and to open opportunities for the growth of sustainable creative economic businesses. The method used was through training and mentoring, which included the stages of counseling, demonstration, direct practice, and evaluation of participants' work. The activity was carried out using a participatory approach, in which participants were actively involved in every stage of the training. Data collection techniques were conducted through observation, interviews, and documentation of the process and results of the activity. The results of the activity showed that the tie-dye tote bag making training was able to improve the participants' knowledge and skills in producing attractive tie-dye tote bag handicraft products and foster entrepreneurial interest in the creative economy sector. The training participants were able to produce tie-dye tote bags that were suitable for use and possessed aesthetic value as well as market potential.